2019
DOI: 10.1101/784280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and mechanism of a Type III CRISPR defence DNA nuclease activated by cyclic oligoadenylate

Abstract: these authors made equal contributions to the work presented. AbstractThe CRISPR system provides adaptive immunity against mobile genetic elements in prokaryotes. On binding invading RNA species, Type III CRISPR systems generate cyclic oligoadenylate (cOA) molecules which act as a second messenger, signalling infection and potentiating a powerful immune response by activating a range of downstream effector proteins that can lead to viral clearance, cell dormancy or death. Only one type of effector enzyme has b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…It is also interesting to note that recent studies reported several Cas12 proteins with strong nickase activities, even against perfectly matching target DNA (60,61). Similarly, the recent discovery of the Can1 nickase that is activated by signalling molecules produced by type III Cas effectors upon target recognition suggests that targeted nicking or target-activated nicking may be a common mechanism among CRISPR-Cas systems to slow phage replication (62). The non-specific nature of the nicking and degradation activities may also be harmful to the host bacteria.…”
Section: Discussionmentioning
confidence: 96%
“…It is also interesting to note that recent studies reported several Cas12 proteins with strong nickase activities, even against perfectly matching target DNA (60,61). Similarly, the recent discovery of the Can1 nickase that is activated by signalling molecules produced by type III Cas effectors upon target recognition suggests that targeted nicking or target-activated nicking may be a common mechanism among CRISPR-Cas systems to slow phage replication (62). The non-specific nature of the nicking and degradation activities may also be harmful to the host bacteria.…”
Section: Discussionmentioning
confidence: 96%
“…For example, binding of cOA3 to NucC, an enzyme whose gene is associated with Type III CRISPR-Cas loci and other prokaryotic defense modules, activates it for dsDNA cleavage (108). A recent study also identified can1 (CRISPR associated nuclease 1) in a genome with a Type III-A CRISPR-Cas system (109). Binding of cOA4 to Can1 activates it for nicking at random sequences of dsDNA (109).…”
Section: Rna-guided Coa Signaling In Type III Crispr-cas Systemsmentioning
confidence: 99%
“…A recent study also identified can1 (CRISPR associated nuclease 1) in a genome with a Type III-A CRISPR-Cas system (109). Binding of cOA4 to Can1 activates it for nicking at random sequences of dsDNA (109). These cOA-activated nucleases may promote immunity by triggering degradation of viral DNA during replication or induce host death before the phage can replicate and infect other cells.…”
Section: Rna-guided Coa Signaling In Type III Crispr-cas Systemsmentioning
confidence: 99%
“…reported several Cas12 proteins with strong nickase activities, even against perfectly matching target DNA (Strecker et al, 2019;. Similarly, the recent discovery of the Can1 nickase that is activated by signaling molecules produced by type III Cas effectors upon target recognition suggests that targeted nicking or target-activated nicking may be a common mechanism among CRISPR-Cas systems to slow phage replication (McMahon et al, 2019). The non-specific nature of the nicking and degradation activities may also be harmful to the host bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the gRNAs can be modified with different chemical groups such as 2'O-Me, 2'-F and bridge nucleic acid substitutions (Basila et al, 2017;Cromwell et al, 2018;Hendel et al, 2015;Jakimo et al, 2017;B. Li et al, 2018;Li et al, 2017;McMahon et al, 2018;Mir et al, 2018;O'Reilly et al, 2019;Rueda et al, 2017;Schubert et al, 2018;Yin et al, 2018Yin et al, , 2017. Several studies show that chemically modifying the gRNA not only improves on-target cleavage but also discriminates against offtargets.…”
Section: Improving Target Specificitymentioning
confidence: 99%